2014
DOI: 10.1177/1742395314537841
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personal communities on the self-management of medication taking: A wider exploration of medicine work

Abstract: Our findings support and extend the conceptualisation of routine medicine-taking as a type of work. Furthermore, we illustrate the involvement of SNMs in aspects of medicine-work. Health professionals should explore and support the role of SNMs in medicine-taking where possible. Future research should explore the implications of network types and compositions on medicine-taking and associated work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 37 publications
4
61
0
Order By: Relevance
“…articulation work through providing the device) and encouragement to 'keep monitoring' and to 'just keep an eye on it' (i.e. emotional work, through encouraging the continued practice) (Cheraghi-Sohi et al 2015) here might be seen as expressions of maternal care, and are in line with long-standing sociological ideas about the gendered aspects of family health work. In another interview a young woman recounted that her husband had bought a monitor for her in part to persuade her to take her blood pressure seriously.…”
Section: Procuring and Providing Devicesmentioning
confidence: 67%
See 3 more Smart Citations
“…articulation work through providing the device) and encouragement to 'keep monitoring' and to 'just keep an eye on it' (i.e. emotional work, through encouraging the continued practice) (Cheraghi-Sohi et al 2015) here might be seen as expressions of maternal care, and are in line with long-standing sociological ideas about the gendered aspects of family health work. In another interview a young woman recounted that her husband had bought a monitor for her in part to persuade her to take her blood pressure seriously.…”
Section: Procuring and Providing Devicesmentioning
confidence: 67%
“…In this case the device does not bring with it a set of health professionals making new connections between clinics and homes. Nevertheless as with technologies provided by the clinic, the use of this consumer health device may rely on family members who undertook articulation, emotional and informational work (Cheraghi-Sohi et al 2015) by gifting, buying or lending monitors and providing encouragement and support for their use. One aspect that emerges in our research which has previously been less in focus is the potential for personal networks to discourage monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few published studies using ego-net or personal network approaches to explore HCPs and informal network members, such as their family and friends, some of whom had healthcare experience. 19 A further study used an ego-net approach to explore roles in 17 The authors used the concept of 'medicines work' to explore the roles of others in enabling medicines taking. They found that personal network members performed tasks such as collecting and monitoring medicines, offering emotional support, and providing information to patients.…”
Section: Ego-net Analysis Of Medicines Managementmentioning
confidence: 99%